2022
DOI: 10.3389/fmicb.2022.985108
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin inhibits pseudorabies virus infection through direct inactivation and activating host antiviral defense

Abstract: Myricetin, a polyhydroxyflavone compound, is one of the main ingredients of various human foods and therefore also known as dietary flavonoids. Due to the continuous emergence of resistant strains of herpesviruses, novel control measures are required. In the present study, myricetin exhibited potent antiviral activity against pseudorabies virus (PRV), a model organism of herpesvirus. The suppression rate could reach up to 96.4% at a concentration of 500 μM in cells, and the 50% inhibitory concentration (IC 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…(Chen et al 2019 ). Studies have revealed that Myricetin can impede pseudorabies virus infection by directly deactivating the virus and stimulating the host's antiviral defense (Hu et al 2022 ). Previous studies have indicated that the main mechanisms of action for Myricetin involve direct viral killing and inhibition of viral adsorption or penetration (Li et al 2020 ; Wang et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Chen et al 2019 ). Studies have revealed that Myricetin can impede pseudorabies virus infection by directly deactivating the virus and stimulating the host's antiviral defense (Hu et al 2022 ). Previous studies have indicated that the main mechanisms of action for Myricetin involve direct viral killing and inhibition of viral adsorption or penetration (Li et al 2020 ; Wang et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the main mechanisms of action for Myricetin involve direct viral killing and inhibition of viral adsorption or penetration (Li et al 2020 ; Wang et al 2023 ). This makes it a promising candidate for preventing virus infections or for use in combination with other drugs targeting viral replication stages (Hu et al 2022 ). Additionally, Quercetin, a flavonoid commonly found in fruits and vegetables, is well-known for its antioxidant, antiviral, antimicrobial, and anti-inflammatory properties (Di Petrillo et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that myricetin, luteolin and kaempferol exhibited an inhibitory effect on herpesvirus infection. Myricetin blocks HSV infection by directly interacting with gD while down-regulating the EGFR/PI3K/Akt signaling pathway [ 37 , 38 ]. To prevent EBV reactivation, luteolin reduces the expressions of the promoters of Zta and Rta [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo experiment was performed as previously described [44]. In brief, a total of 39 female BALB/c mice (4-6 weeks old) were randomly divided into three groups: the control group, the PRV-infected group, and the PRV-infected with bufalin-treated group.…”
Section: The Effect Of Bufalin On Prv Infection In Balb/c Micementioning
confidence: 99%